2017
DOI: 10.1177/2053168017712885
|View full text |Cite
|
Sign up to set email alerts
|

Militarization and police violence: The case of the 1033 program

Abstract: Does increased militarization of law enforcement agencies (LEAs) lead to an increase in violent behavior among officers? We theorize that the receipt of military equipment increases multiple dimensions of LEA militarization (material, cultural, organizational, and operational) and that such increases lead to more violent behavior. The US Department of Defense 1033 program makes excess military equipment, including weapons and vehicles, available to local LEAs. The variation in the amount of transferred equipme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 13 publications
0
65
0
1
Order By: Relevance
“…Although these uses reflect larger trends in the changing responsibilities of police in general (Beck and Goldstein, ; Simon, ), the war on drugs and the ability to maintain a superior force in the threat of potential violence remain the primary initial reasons for acquiring property from the 1033 Program (Apuzzo, ; DLA, ; Grasso, ; Iannelli, ). Finally, regardless of how departments use MRAPs and other militarized property, the acquisition of such materiel is associated with harsh and overbearing policing in both police practice (Delehanty et al., ) and public opinion (Carriere and Encinosa, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these uses reflect larger trends in the changing responsibilities of police in general (Beck and Goldstein, ; Simon, ), the war on drugs and the ability to maintain a superior force in the threat of potential violence remain the primary initial reasons for acquiring property from the 1033 Program (Apuzzo, ; DLA, ; Grasso, ; Iannelli, ). Finally, regardless of how departments use MRAPs and other militarized property, the acquisition of such materiel is associated with harsh and overbearing policing in both police practice (Delehanty et al., ) and public opinion (Carriere and Encinosa, ).…”
Section: Methodsmentioning
confidence: 99%
“…Even though there is a growing body of scholars who argue that participation in the 1033 Program makes an excellent test case for theories of police militarization (Ajilore, ; Bove and Gavrilova, ; Dansky, ; Delehanty et al., ; Harris et al., ; McQuoid and Vitt, ; Radil, Dezzani, and McAden, ), it is not an exhaustive indicator of police militarization . We focus on the 1033 Program, however, because accessing materiel such as weaponry, vehicles, and uniforms is an early and often necessary step for many LEAs toward further militarization in the dimensions of language and terminology, organizing using military principles, and practicing military‐style tactics (Ajilore, ; Insler, McMurray, and McQuoid, ; Kraska, ; Phillips, ).…”
Section: Police Militarization and The 1033 Programmentioning
confidence: 99%
“…In the wake of September 11, 2001 terror attacks, additional funding streams allowed departments to acquire new technologies and equipment, further promoting the militarization of local law enforcement (Balko ; Chaffetz and Cummins ). Radil et al (: 208) and Delehanty et al () noted that 80 percent of U.S. counties had received equipment through the 1033 Program between 2006 and 2013 . To date, over 8000 law enforcement agencies, representing roughly 45 percent of all police agencies in the United States, have participated in the Program (Defense Logistics Agency ).…”
Section: A Context To Examine the Empowerment Hypothesis: Police Milimentioning
confidence: 99%
“…Insler et al suggest that such findings may indicate that the 1033 Program participation has a negative effect on social solidarity in the United States. Delehanty et al () used county‐level data on police killings of civilians and dogs in Connecticut, Maine, Nevada, and New Hampshire in 2013 to find a positive association between the 1033 Program participation and police violence. Lawson () conducted a similar study using a sample of all LEAs that participated in the 1033 Program and found that increases in the value of the 1033 Program materials obtained were associated with increases in the LEA‐level counts of police killings but not with increases in the odds of a police killing occurring.…”
Section: Empirical Studies Of Police Militarizationmentioning
confidence: 99%
“…Assessing the impact of police militarization is important beyond crime control. Some indicators of police militarization appear to be associated with racialized trends in policing as opposed to actual threats to police (Ajilore, ; Mummolo, ; Ramey & Steidley, ) as well as with the increased the use of lethal force by the police (Delehanty et al, ; Lawson, ). Research also suggests that the public interactions with and perceptions of police who display signs of militarism are less amiable (Bell, ; Mummolo, ).…”
Section: The State Of Research On Police Militarizationmentioning
confidence: 99%